Stable tissue oxygen cerebral perfusion pressure (stoCPP): Proof of concept for a novel method for the assessment of optimum cerebral perfusion pressure in severe traumatic brain injury - Toby Jeffcote; Sung Wook Chung; Anis Chaba; Kuan-Ying Lu; Camila R. Battistuzzo; Jasmin Board; Emma-Leah Martin; D. James Cooper; Andrew A. Udy (Journal of Clinical Monitoring and Computing, 2026)
Abstract To demonstrate a method for the identification of safe cerebral perfusion pressure (CPP) in patients with severe traumatic brain injury using brain tissue oxygen (PbtO₂) readings as a surrogate marker of cerebral blood flow. Retrospective analysis of prospectively collected data from patients with severe TBI (sTBI). A total of 9 patients with sTBI enrolled in the BONANZA-GT trial with continuous monitoring of mean arterial blood pressure (MAP), intracranial pressure (ICP), cerebral perfusion pressure (CPP) and PbtO₂. MAP, ICP, CPP and high frequency PbtO₂ signals were continuously recorded. stoCPP was calculated as the coefficient of determination (r²) of short-term changes in PbtO₂ regressed on short-term changes in CPP within non-overlapping 144-second correlation windows, assigned to 5-mmHg CPP bins using a window-median binning approach. Algorithm parameters were optimised using Bayesian optimisation with a composite scoring function benchmarked against CPPopt. Per-subject r² thresholds were derived by block-shuffle calibration (median 0.12, range 0.06–0.26). stoCPP was successfully generated for all 9 patients from raw unfiltered data. The lower limit of the stoCPP range (LLstoCPP) was defined in approximately 22% of analysis windows, as it is identifiable only during episodes of CPP perturbation below the stable range. CPPopt point estimates fell within the stoCPP range in 76.2% of observations, with a mean stoCPP width of 22.8 mmHg. Bland-Altman analysis of lower bounds ( n = 102 independent estimates) demonstrated a mean bias of 4.1 mmHg (SD 7.3 mmHg; 95% limits of agreement − 10.1 to + 18.4 mmHg). Trough depth characteristics of the stoCPP range degraded significantly with temporal misalignment of the PbtO₂ signal (Kendall’s W = 0.557, p < 0.001), supporting the physiological basis of the method. stoCPP was defined in all patients from raw unfiltered data using Bayesian-optimised parameters and per-subject calibrated r² thresholds, and demonstrated close correspondence with CPPopt. We propose further validation of this method utilising alternative PbtO₂ probe types and larger patient cohorts to assess the validity of time below LLstoCPP as a marker of ischaemia and determinant of outcome in sTBI.